2011
DOI: 10.4103/0970-0358.85354
|View full text |Cite
|
Sign up to set email alerts
|

Staged tendon grafts and soft tissue coverage

Abstract: The objective of the two-staged flexor tendon method is to improve the predictability of final results in difficult problems dealing with tendon reconstruction. This article reviews the evolution and benefits of this procedure. It also considers the use of the technique to help deal with problems requiring pulley and skin reconstruction simultaneously with re-constituting the flexor tendon system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The authors reported an unsatisfactory range of motion at the MCP joint in six out of 14 patients. This indicates that the tunnels created by the rods provide better tendon gliding, and this has been observed in two-staged flexor tendon reconstruction (Elliot, 2011). (2000) 1 Groin flap Flexor superficialis tendon transfer 15° extension lag, 30° limitation of flexion Bevin and Hothem (1978) 2…”
Section: Discussionmentioning
confidence: 93%
“…The authors reported an unsatisfactory range of motion at the MCP joint in six out of 14 patients. This indicates that the tunnels created by the rods provide better tendon gliding, and this has been observed in two-staged flexor tendon reconstruction (Elliot, 2011). (2000) 1 Groin flap Flexor superficialis tendon transfer 15° extension lag, 30° limitation of flexion Bevin and Hothem (1978) 2…”
Section: Discussionmentioning
confidence: 93%
“…Grafting of flexor and extensor tendons of the hand is especially challenging since restoration of function and dexterity require both a strong repair and effective gliding. 42 Tendon autografts and allografts are also used in anterior cruciate ligament reconstruction, which is often more successful than direct repair. Autografts are preferred to allografts due to better tissue integration, recellularization, and revascularization; however, donor site morbidity can be significant.…”
Section: The Clinical Importance Of Tendon and Ligament Bioreactorsmentioning
confidence: 99%
“…Originally, upon examination of the autoacceleration of the conversion-time curves, it was believed that termination reaction only became diffusion controlled at some monomer conversion greater than zero [28] and that this occurred when the polymer chains were sufficiently entangled (with a sufficient number of physical entanglement points). [25] Besides that, Hamielec and Tobita [25] stated that the bimolecular termination reactions may be diffusion controlled even at zero monomer conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Originally, upon examination of the autoacceleration of the conversion–time curves, it was believed that termination reaction only became diffusion controlled at some monomer conversion greater than zero and that this occurred when the polymer chains were sufficiently entangled (with a sufficient number of physical entanglement points)…”
Section: Resultsmentioning
confidence: 99%